Pengaruh Kesejahteraan, Budaya Sekolah dan Disiplin Kerja Terhadap Komitmen Guru Dikdasmen Daerah Muhammadiyah Kota Medan - Luliadi Luliadi; Indra Prasetia; Sri Nurabdiah Pratiwi (EduTech: Jurnal Ilmu Pendidikan dan Ilmu Sosial, 2023)
This study aims to examine the effect of welfare, school culture and work discipline on the commitment of elementary school teachers in the Muhammadiyah area of Medan. This study uses quantitative research methods, namely field research using scientific studies of scientific experts. the population in this study amounted to 115 people, research methods. The data in this study are primary data. Data collected by using a questionnaire. The analytical method uses multiple linear regression models to test the hypothesis simultaneously using the F test and partially using the t test. The results of testing using SPSS obtained the regression equation using the computer output above obtained the multiple regression equation as follows: a constant of 0.05; welfare coefficient (X1) of 9.115; school culture coefficient (X2) of 7.825, and work discipline coefficient (X3) of 8.158; teacher commitment coefficient (Y) of 8.158 Thus the regression line equation is Y = 0.05 + 0.496X1 + 0.610X2 + 0.388X3. If the independent variable increases by 1% then the teacher's commitment will increase. The results of the hypothesis test tcount 0.7315 with a significant probability of 0.000 less than the level of significance (level of significance) α = 0.05, the research variable is welfare obtained by ttest 7.288 with a probability of 0.000 less than the level smaller than the level of confidence (level of significant ) α = 0.05. the school culture variable is obtained by the thumg test 8.384 with a probability of 0.000 which is less than the level of significance α = 0.05. The variable of work discipline is obtained by a thump test of 7.530 with a probability of 0.000 which is less than the level of significance α = 0.05. So the decision taken was to reject H0 and accept Ha, which means that welfare, school culture, work discipline have a positive and significant effect on the commitment of elementary school teachers in the Muhammadiyah area of Medan city